Effect of Zoom on English Speaking for EFL Students - Andewi, Widi; Trinovita, Diyah (LinguaEducare: Journal of English and Linguistic Studies, 2024)
This study investigates the impact of using Zoom as a learning platform on the English-speaking proficiency of undergraduate students. A quasi-experimental research design was employed, comparing an experimental group that attended English-speaking classes via Zoom with a control group that participated in traditional face-to-face instruction. The participants were 60 undergraduate students from Institut Bakti Nusantara in Lampung, Indonesia, selected using a purposive sampling technique to ensure similar baseline English proficiency levels. The primary instrument for assessing speaking proficiency was a standardized oral examination administered as both a pre-test and post-test. Data collection included these tests and supplementary surveys and semi-structured interviews to capture students' experiences and perceptions. Quantitative data were analyzed using paired sample t-tests, independent sample t-tests, and Analysis of Covariance (ANCOVA) to evaluate improvements within and between groups. Qualitative data were analyzed thematically. The results revealed significant improvements in speaking proficiency for both groups, with the Zoom-based group showing a significantly higher improvement than the control group. These findings suggest that Zoom's interactive features and flexibility can effectively enhance English-speaking skills. The study implies that digital platforms like Zoom can be integrated into English language teaching to create more engaging and supportive learning environments, promoting speaking proficiency. Future research could explore the impact of such platforms on other language skills and across diverse educational contexts.